1976
DOI: 10.1007/bf01219511
|View full text |Cite
|
Sign up to set email alerts
|

Effects of streptozotocin in vitro on proinsulin biosynthesis, insulin release and ATP content of isolated rat islets of Langerhans

Abstract: Summary. Proinsulin synthesis, insulin release and intracellular ATP concentrations were measured in isolated rat islets of Langerhans under control conditions of in vitro incubation and after treatment with several concentrations of streptozotocin for different periods of time. It was found that streptozotocin inhibited proinsulin synthesis, as well as insulin release, in a time and concentration dependent manner. The characteristics of the inhibition of these two processes were similar in general terms, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 35 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…A protecting effect of glucose against the action of alloxan has been shownboth in vivo (81) and in vitro (82), whereas the action of streptozotocin has been described not to be affected by glucose (61,62). HoweVer, our recent study also revealed that the inhibitory effects on proinsulin synthesis not 0oo) only of alloxan but also of streptozotocin are (47) significantly lessened by glucose.…”
Section: High Glucose Protects Against Inhibition Of Proinsulin Synthmentioning
confidence: 69%
See 1 more Smart Citation
“…A protecting effect of glucose against the action of alloxan has been shownboth in vivo (81) and in vitro (82), whereas the action of streptozotocin has been described not to be affected by glucose (61,62). HoweVer, our recent study also revealed that the inhibitory effects on proinsulin synthesis not 0oo) only of alloxan but also of streptozotocin are (47) significantly lessened by glucose.…”
Section: High Glucose Protects Against Inhibition Of Proinsulin Synthmentioning
confidence: 69%
“…On the other hand, it is known that streptozotocin, a typical diabetogenic agent, depresses NAD content in pancreatic islets and inhibits proinsulin synthesis (60,61). As nicotinamide prevents these effects of streptozotocin (62)(63)(64), it has been so far considered that streptozotocin impairs NAD synthesis in islets to cause diabetes (65,66).…”
Section: A New Aspect To Experimental Diabetesstreptozotocin Andmentioning
confidence: 99%
“…STZ-treated Parp Ϫ/Ϫ mice showed a delayed onset of mild but transient hyperglycemia. Because exposure of isolated islets to STZ in vitro also results in a decrease of glucose oxidation to CO 2 (9) and insulin synthesis (25), in addition to the direct DNA damage, these effects may contribute to the delayed and slight ␤-cell dysfunction also seen in Parp Ϫ/Ϫ mice. Blood insulin levels (data not shown) and glucose concentrations were similar in untreated Parp Ϫ/Ϫ and Parp ϩ/ϩ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Pork monocomponent insulin was iodinated by the chloramine T method to a specific activity of 150-180 ~tCi/~g (0.4-0.5 atom of iodine per molecule, purified on Sephadex G 50 [30], and tested prior to use for its ability to bind to rat liver plasma membranes [12]. Pork monocomponent insulin, crystalline beef insulin, pork proinsulin were obtained from Novo, Novoall6, DK-2880 Bagsvaerdt (Denmark).…”
Section: Chemica~mentioning
confidence: 99%